DETERMINATION OF EARLY DIAGNOSTIC AND NEUROLOGICAL SIGNS IN PATIENTS WITH SYSTEMIC LUPUS ERYTHEMATOSUS (World Bulletin of Public Health, 2023)
In the last years the growth of autoimmune diseases with systemic lupus erythematosus takes a special place; possibilities of modern diagnostics, population awareness, factors of environmental disadvantage (Priaralie), consequences of COVID 19 have become the reflection on the character of the disease and its complications.
Keywords: clinical and neurological examination; systemic lupus erythematosus